(untitled) (Analysis in Theory and Applications, 2016)
We know that the Box dimension of f(x)C^1[0,1] is 1. In this paper, we prove that the Box dimension of continuous functions with bounded variation is still 1. Furthermore, Box dimension of Weyl fractional integral of above function is also 1.